ANALISIS FAKTOR RISIKO SINDROM METABOLIK PADA PEKERJA UNIT PEMBANGKITAN PRIOK PT. X TAHUN 2021 - Dian Surya Pratama; Indri Hapsari Susilowati (JKM (Jurnal Kesehatan Masyarakat) Cendekia Utama, 2022)
Occupational Health is one of the efforts to promote and maintain the highest level of physical, mental and social health of workers in all occupations, prevention of problems related to workers due to their working conditions, protection of workers in their work from risks caused by factors detrimental to health, placement and maintenance of workers in a work environment that is adapted to their physiological and psychological abilities. This study aims to analyze the risk factors for metabolic syndrome of workers at the Priok Generation Unit PT. X. 2021. This study used a cross sectional method, with a sample of 100 respondents to workers at the Priok Generation Unit PT. X. Data analysis was carried out univariate, bivariate using chi square test and multivariat with logistic regression method using SPSS software version 23. The research instrument has been tested for validity and reliability in accordance with the rules and obtained a certificate of passing the ethical review with Number: Ket-552 /UN2.F10.D11/PPM.00.02/2021 issued by the research ethics committee of the Faculty of Public Health, University of Indonesia. The components of the metabolic syndrome most experienced by research respondents were an increase in fasting blood sugar, hypertension, an increase in triglycerides, the occurrence of central obesity and a decrease in HDL fat levels in the blood. This study shows that the risk factors that are significantly related to the occurrence of metabolic syndrome in workers are age, education level, smoking status and physical activity. Based on multivariate modeling with 11 modeling test stages, it was found that the personal education factor is one of the most dominant factors in the occurrence of metabolic syndrome. The level of education is one of the dimensions that describes a person's level of knowledge and insight, so the higher the level of knowledge education to carry out a healthy lifestyle to prevent the occurrence of metabolic syndrome, the better.